Is it possible to decorate graphical software design and architecture models with qualitative Information?-An experiment. - Bratthall, L.
Software systems evolve over time and it is often difficult to maintain them. One reason for this is that often it is hard to understand the previous release. Further, even if architecture and design models are available and up to date, they primarily represent the functional behavior of the system. To evaluate whether it is possible to also represent some nonfunctional aspects, an experiment has been conducted. The objective of the experiment is to evaluate the cognitive suitability of some visual representations that can be used to represent a control relation, software component size and component external and internal complexity. Ten different representations are evaluated in a controlled environment using 35 subjects. The results from the experiment show that representations with low cognitive accessibility weight can be found. In an example, these representations are used to illustrate some qualities in an SDL block diagram. It is concluded that the incorporation of these representations in architecture and design descriptions is both easy and probably worthwhile. The incorporation of the representations should enhance the understanding of previous releases and, hence, help software developers in evolving and maintaining complex software systems.
Keywords: SDL block diagram; Architecture models; Graphical software design; Qualitative information; Software component size; Software evolution; Software maintenance; Software quality representation; Software systems